Ellis-van Creveld Syndrome - K Rajendra; T K Ramamurthy; K Gopikrishna; G V Ramachandra Reddy; K Srinivas; S Patil (Wolters Kluwer Medknow Publications, 2010)
Ellis-van Creveld syndrome also known as chondroectodermal dysplasia is a rare genetic disorder of the skeletal dysplasia type, first described by Richard WS Ellis and Simon van Creveld in 1940. The syndrome manifests with several skeletal anomalies, oral mucosal and dental anomalies, congenital cardiac defects, nail dysplasia and polydactyly of one or both limbs. It is caused by mutation of EVC1 and EVC2 genes located in a head-to-head configuration on chromosome 4p16, which has been identified as the causative. The EVC phenotype is variable and affects multiple organs. The presence of oral mucosal and dental alterations, like the presence of numerous frenulum, oligodontia, bellshaped anterior teeth, hypoplastic erupted teeth with high-caries index, will confirm the diagnosis of Ellis-van Creveld syndrome and hence its importance to dentists.